Adapter Protein SH2-Bβ Undergoes Nucleocytoplasmic Shuttling: Implications for Nerve Growth Factor Induction of Neuronal Differentiation - Chen, Linyi (American Society for Microbiology, 2004)
The adapter protein SH2-B has been shown to bind to activated nerve growth factor (NGF) receptor TrkA and has been implicated in NGF-induced neuronal differentiation and the survival of sympathetic neurons. However, the mechanism by which SH2-B enhances and maintains neurite outgrowth is unclear. We examined the ability of truncation mutants to regulate neuronal differentiation and observed that certain truncation mutants localized in the nucleus rather than in the cytoplasm or at the plasma membrane as reported for wild-type SH2-Bβ. Addition of the nuclear export inhibitor leptomycin B caused both overexpressed wild-type and endogenous SH2-Bβ to accumulate in the nucleus of both PC12 cells and COS-7 cells as did deletion of a putative nuclear export sequence (amino acids 224 to 233) or mutation of two critical lysines in that sequence. Deleting or mutating the nuclear export signal caused SH2-Bβ to lose its ability to enhance NGF-induced differentiation of PC12 cells. Neither the NGF-induced phosphorylation of ERKs 1 and 2 nor their subcellular distribution was altered in PC12 cells stably expressing the nuclear export-defective SH2-Bβ(L231A, L233A). These data provide strong evidence that SH2-Bβ shuttles constitutively between the nucleus and cytoplasm. However, SH2-Bβ needs continuous access to the cytoplasm and/or plasma membrane to participate in NGF-induced neurite outgrowth. These data also suggest that the stimulatory effect of SH2-Bβ on NGF-induced neurite outgrowth of PC12 cells is either downstream of ERKs or via some other pathway yet to be identified.